Does body composition relate to active drag during arms-only front crawl swimming in male collegiate swimmers? - Narita, K.; Washino, S.; Kadi, T.; Kanehisa, H.; Mankyu, H.; Fujita, E. (Journal of Science and Medicine in Sport, 2025)
Objectives Fat tissue does not directly contribute to an increase in propulsive force in swimming, though it has the potential to indirectly enhance swimming performance by reducing active drag as the specific gravity of fat tissue is lower than that of water. However, the relationship between body composition and active drag has not been elucidated. This study aimed to evaluate how body composition relates to active drag during arms-only front crawl swimming.